Identification of Vietnamese lizards - Tien, Dao Van (Academia Journal of Biology, 2013)
In the paper, there is a list (with vernacular names) of Vietnamese lizards known at present (77 spp) including 6 spp recently revealed in North Vietnam (Hemidactylus karenorum, Draco taenioplerus, D. volans?, Eumeces elegans, Sphenomorphus indicum, Takydromus wolteri). A key to species is also included